2018
DOI: 10.1038/s41398-018-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fear memories and brain glucose metabolism (18F-FDG-PET) following sub-anesthetic intravenous ketamine infusion in Sprague-Dawley rats

Abstract: Ketamine is a multimodal dissociative anesthetic, which provides powerful analgesia for victims with traumatic injury. However, the impact of ketamine administration in the peri-trauma period on the development of post-traumatic stress disorder (PTSD) remains controversial. Moreover, there is a major gap between preclinical and clinical studies because they utilize different doses and routes of ketamine administration. Here, we investigated the effects of sub-anesthetic doses of intravenous (IV) ketamine infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 56 publications
2
39
2
Order By: Relevance
“…Furthermore, the results of IV administration depend on whether the drug is administered through a rapid bolus (one-time IV injection) or a prolonged infusion with a mechanical syringe pump. Consistent with these observations, a preclinical study observed that a ketamine bolus (2 and 5 mg/kg, IV) produced rapid and robust dissociative stereotypy [ 24 ], while a ketamine infusion (10 mg/kg, IV) over 2 h produced hypo-locomotor activity (a sign of sedation and analgesia) in rats [ 20 , 22 ]. Because the IV route is rarely used in preclinical studies, it is critical to utilize the IV ketamine administration technique to a larger extent in preclinical research in order to better model the clinically relevant route of ketamine administration.…”
Section: Effects Of Ketamine On Fear Memorymentioning
confidence: 81%
See 3 more Smart Citations
“…Furthermore, the results of IV administration depend on whether the drug is administered through a rapid bolus (one-time IV injection) or a prolonged infusion with a mechanical syringe pump. Consistent with these observations, a preclinical study observed that a ketamine bolus (2 and 5 mg/kg, IV) produced rapid and robust dissociative stereotypy [ 24 ], while a ketamine infusion (10 mg/kg, IV) over 2 h produced hypo-locomotor activity (a sign of sedation and analgesia) in rats [ 20 , 22 ]. Because the IV route is rarely used in preclinical studies, it is critical to utilize the IV ketamine administration technique to a larger extent in preclinical research in order to better model the clinically relevant route of ketamine administration.…”
Section: Effects Of Ketamine On Fear Memorymentioning
confidence: 81%
“…Rats that received ketamine (10 mg/kg, IP) after the reactivation of contextual fear had less freezing the following day compared to those that received 20 mg/kg, indicating that a lower ketamine dose impaired the reconsolidation of contextual fear memory [ 11 ]. Radford and colleagues found a similar result when ketamine infused at varying doses (2, 10, and 20 mg/kg, IV, 2 h) after fear conditioning produced an inverted-U-shaped dose–response curve, such that the 10 mg/kg dose produced a greater enhancement of fear memory than the low and high doses in rats [ 22 ]. The high-dose ketamine infusion (20 mg/kg, IV, 2 h) increased dissociative behavior and hyper-locomotion, while the medium-dose ketamine infusion (10 mg/kg, IV, 2 h) produced hypo-locomotion and sedative-like effects [ 22 ].…”
Section: Effects Of Ketamine On Fear Memorymentioning
confidence: 85%
See 2 more Smart Citations
“…The preclinical antidepressant-like effects of mGlu2/3 receptor antagonists, however, is not supported by clinical testing of mGlu2/3 receptor antagonists (NCT01457677, ClinicalTrials.gov) in patients with MDD (Lawrence, 2015). Also in contradistinction to orthosteric mGlu2/3 receptor agonists like LY354740, the evidence for anxiolytic-like preclinical effects of mGlu2/3 receptor antagonists (Bespalov et al, 2008;Chaki et al, 2004;Iijima et al, 2007;Johnson et al, 2003;Yoshimizu et al, 2006) and NMDA channel blockers like ketamine (Clifton et al, 2018;Engin et al, 2009;Fraga et al, 2018;Hayase et al, 2006;Kilic et al, 2014;Loss et al, 2012;McGowan et al, 2017;Pietersen et al, 2006;Radford et al, 2018;Silvestre et al, 1997;Zhang et al, 2015) are quite mixed . Preclinical antidepressant-like effects of LY354740 is also quite limited compared to the robust preclinical anxiolytic-like effects of the mGlu2/3 receptor agonist LY35470 (Ferris et al, 2001;Helton et al, 1998;Monn et al, 1997;Rorick-Kehn et al, 2006;Shekhar and Keim, 2000;Spooren et al, 2002;Tizzano et al, 2002).…”
Section: Discussionmentioning
confidence: 99%